Regulation when platforms are layered - William Lehr; David Clark; Steve Bauer (International Telecommunications Society (ITS), 2019)
This paper represents a synthesis and extension of earlier work, applying the Lehr & Sicker (2018a,b) regulatory approach to the layered platform model of Claffy & Clark.3 Today's Internet ecosystem is comprised of multiple digital network platforms organized into a multi-layer architecture. Lower layer IP platforms provided by access and backbone ISPs collectively support the Internet, on which complementors may build higher-layer platforms, such as the digital network platforms provided by Google, Amazon, Facebook and Apple ("GAFA"). Each of these firms control and operate multiple platforms operating at multiple layers that comprise ecosystems within the larger Internet ecosystem to which they belong. Herein, we explore the viability of the Lehr & Sicker regulatory framework for a reformed and newly authorized FCC with authority to address the regulatory challenges confronting policymakers in this multi-layered ecosystem.
Keywords: 330